Omental Infarction after Infectious Uterine Underwent Caesarian Section: A Case Report - Shahraki, Ahmad Reza; Abaee, Reza; Shahraki, Elham (International Journal of Innovative Research in Medical Science, 2023)
Omental infarction is a rare disease that affects the entire omentum or a segment of the greater omentum. It presents as acute abdominal pain mainly in the right lower quadrant or right flank. Left-sided omental torsion is infrequent and it is rarely preoperatively diagnosed. Omental infarction is a differential diagnosis in the acute abdomen. As most cases of omental infarction can be adequately diagnosed via computed tomography, a conservative treatment strategy for patients without complications should be considered in order to avoid any unnecessary surgical intervention. Our case was a middle age woman with abdominal pain that surgery showed omental infarction after infectious cesarean section. After surgery patient discharged successfully. Although the classical treatment of omental infarction is surgery, more recently the conservative management has been suggested. Thus, we believe that the knowledge of the characteristic imaging findings is essential for establish a correct preoperative diagnosis, which can avoid unnecessary surgical intervention.